Impact of Marital Status on Survival in Patients with Ocular and Periocular Malignancies: A Retrospective Analysis of 3159 Patients from the SEER Database - Loya A (Dove Medical Press, 2020)
Asad Loya,1 Talha Ayaz,2 Christina Y Weng3 1School of Medicine, Baylor College of Medicine, Houston, TX, USA; 2School of Medicine, University of Texas Medical Branch at Galveston, Galveston, TX, USA; 3Department of Ophthalmology,Cullen Eye Institute, Baylor College of Medicine, Houston, TX, USACorrespondence: Christina Y WengDepartment of Ophthalmology, Cullen Eye Institute, Baylor College of Medicine, Houston, TX, USATel +1 713 798-6100Email christina.weng@bcm.eduBackground: An ocular or periocular malignancy can profoundly impact patients’ lives as they cope with the challenges of a potentially life-threatening diagnosis and the exhaustive treatment process it entails. An amalgam of biopsychosocial factors can influence prognosis. This study aims to determine whether marital status impacts the long-term survival of patients with these malignancies.Methods: A retrospective analysis of the Surveillance, Epidemiology, and End Results (SEER) database was performed. Patients with ocular and periocular malignancies diagnosed between 1973 and  2015 were included. The association between survival and marital status was assessed using univariate and multivariate Cox regression. Adjusted covariates included demographic, tumor, and treatment data.Results: A total of  3159 patients with a mean±SD follow-up period of 6.47± 4.62 (range 0– 17.9) years were studied. At the time of diagnosis, 63.4% (2004/3159) of the cohort were married, 12.9% (409/3159) were single, 16.3% (514/3159) were widowed, and 7.3% (232/3159) were divorced. The mean±SD age of the cohort was 64.4± 15.17 (range 26– 100) years, with histology distributed as 14.6% (462/3159) melanoma, 84.5% (2669/3159) lymphoma, and 0.9% (28/3159) plasmacytoma. Adjusted all-cause mortality risk was higher in single (HR, 1.885, 95% CI 1.535 to 2.314; P< 0.001), widowed (HR, 1.382, 95% CI 1.169 to 1.635; P< 0.001), and divorced (HR, 1.637, 95% CI 1.271 to 2.109; P< 0.001) individuals compared to married individuals. Similarly, adjusted cause-specific mortality risk was higher in single (HR, 1.835, 95% CI 1.332 to 2.528; P< 0.001), widowed (HR, 1.376, 95% CI 1.025 to 1.847; P=0.033), and divorced (HR, 1.873, 95% CI 1.272 to 2.758; P=0.001) individuals compared to married individuals.Conclusion: Unmarried (single, widowed, and divorced) individuals with ocular or periocular malignancies have unmet social support needs resulting in poorer long-term outcomes. Understanding the prognostic role of such psychosocial factors is necessary to improve the identification of and care for patients with inadequate support.Keywords: oncology, ocular, cancer, SEER, relationship, database